Satellite navigation interference monitoring in the Baltic and North Seas - Azevedo de Vasconcelos, Thiago; Kurz, Lothar; Konovaltsev, Andriy; Ehlers, Tobias; Meurer, Michael (The International Hydrographic Review, 2025)
The threats scenario of radio-frequency interference in maritime domain has been assessed through the results of measurement campaigns in the Baltic and North Seas. This work presents the monitoring equipment deployed for real-time interference detection and displaying capabilities, allowing live assessment of the interference impacts. The measurement system and the results of the post-campaign processing of the recorded data are described characterizing the observed interference signals and the impact on the satellite-based navigation of GPS L1/L5 and Galileo E1/E5a open services. The geographical distribution of the interference events and the severity of the situation is discussed.